Technology Utilization in the Field of School Counseling: An Action Research Study - Creamer, Michael B. (Valdosta State University College of Education, 2002)
The purpose of this study was to analyze how school counselors utilize technology in their school counseling programs and to generate methods for encouraging such use within the Georgia School Counselors Association. Several variables were examined in this study. The main variable examined was counselor use of technology. Counselor use of technology was defined as the type, frequency, and location of technology use by the counselor. Other variables that were examined that influence counselor adoption and use of technology included administrator support for technology use, funding to acquire technology, access to the technology, level of comfort using technology, college training for using technology in counseling, motivation to use technology, counselor willingness to participate in staff development, and school location - rural or urban. The participants of this study included 145 elementary, middle, and high school counselors from eleven states. The instruments used in the study assessed the counselors' frequency of technology use for clerical tasks, teacher training, parent training, individual counseling, group counseling, classroom guidance, communication, and Internet searches. The study discovered that school counselors are using technology for a variety of tasks from the mundane clerical tasks to innovative interactive lessons. In addition, it was concluded that school counselors are interested in staff development on technology if it can benefit their programs. Many participants involved in this research utilize technology in innovative ways. The innovative ideas discovered in this study have assisted me in designing professional development for GSCA, and other counselors, on innovative uses of technology.